Nowdays, greenhouse is becoming popular in tropical country for plant cultivations, which the main reason is fbrplant protection against unwanted distwbances i.e. from heavy rainfall, wind, pest and so on. Since most of the greenhouse are covered with transparence material such as glass plate, plastic sheet, fiberglass etc., the greenhouse effect will take place accordingly causing a temperature rise that is usually higher than that of the outside. It turns out that this rising temperature becom - Eko D Saptoto; Budi I Setiawan; Marzan A Iskandar (Jurnal Keteknikan Pertanian, 1997)
Nowdays, greenhouse is becoming popular in tropical country for plant cultivations, which the main reason is fbrplant protection against unwanted distwbances i.e. from heavy rainfall, wind, pest and so on. Since most of the greenhouse are covered with transparence material such as glass plate, plastic sheet, fiberglass etc., the greenhouse effect will take place accordingly causing a temperature rise that is usually higher than that of the outside. It turns out that this rising temperature becomes a major problem that will have negative effects on the plant growth. This research aims to control the temperature in the greenhouse by applying a Fuzzy Logic Controller (FLC), first by maintaining a constant temperature in the greenhouse and secondly, by trying to equalize the temperature in the greenhouse to that of the outside. The experiment was canied.out at a small scale with the greenhouse dimension of (1 00 x 120 x 100) c d Heet fnun the greenhouse was expelled using an exhaust fan. The power of the fan was: contfv&d.by the FLC subjected to the real temperaturn changes with time. The results sh~wtha t the FLC could pe~formg oad function of a temperature controller for the greenhouse.. It couM control the temperature in the greenhouse under the expected conditions end explained the energy consumption throughout the process.